Abhi Praya Nusantara Shoes Cleaner: Langkah mudah merawat sepatu dengan sabun pembersih terbaru - Utomo, Bagus Satrio Budi; Prayoga, Rizky Dwi; Azkiya, Muhammad Fadzlulloh; Adzani, Wanasa Rahmat Akbar (Maliki Interdisciplinary Journal, 2024)
Currently, shoes are not only used as footwear whose purpose is to protect the feet when carrying out daily activities, but currently shoes have also become a fashion trend that many people use to support their appearance. Therefore, when using shoes, of course they must receive good care so that they can support a more attractive appearance. This article will discuss shoe care products that are able to clean and care for shoes with several other advantages, which will be a practical solution in terms of shoe care.